Ureterovaginalfistel, a distal portion complication of the ureter injury - Case report - Prawito Singodimedjo, Prawito Singodimedjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
In the female complication of the distal portion of the ureter injury is the ureterovaginal fistula, seen most often after the Wertheim hysterectomy. The true incidence of the disease is difficult to ascertain in the literature. Incontinence isthe first symptom of the ureterovaginal fistula patient. An IVP, RPG, cystography, cystoscopy and double dye test investigations are to be advocated for diagnosis of the disease.Ureterovaginal fistula is repaired by standard ureteroneocystostomy, incorporating an antirefluxing submucosal tunnel.Key Words: Wertheim hysterectomy - ureterovaginal fistula - incontinence - ureteroneocystostomy - ureter injury